Aspects of administration of agricultural wildlife damage and African swine fever - Battay, Márton; Nógrádi, Anna; Illés, Bálint Csaba; Marosán, Miklós (Animal welfare, Ethology and Housing Systems (AWETH), 2019)
In areas where, due to infection, there is a hunting ban in effect, the possibilities to prevent wildlife damage are limited for hunting associations. Because of this the compensation offered by the state plays a massive role in the management of the negative economic effects of African swine fever. Due to this compensation of the state an important part of the negative external effect is internalized, but this intervention also influences hunting associations in the long term. Under normal circumstances, part of the actual wildlife damage is not, or just partially compensated by hunting associations. This is usually due to the relationship of the parties and the local practice. The compensation of the state can alter this, since the cost of the compensation is not payed by the hunting associations, but the state. After the lifting of the epidemiolgical restrictions hunting associations will have to fulfill their obligations in this transformed situation.